Formula Detektif Klasik pada Cerita Anak The Secret Seven-Sapta Siaga: Kajian Formula John G. Cawelti - Putri, Yuli Aisyah; Indriyani, Jiphie Gilia (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The children’s story The Secret Seven-Sapta Siaga 6th edition is a detective genre children’s story written by Enid Blyton. This research on children’s stories was conducted to reveal how the detective genre formula is found in the children’s book The Secret Seven-Sapta Siaga. This research is a qualitative descriptive study with a review of John G. Cawelti’s classic detective formula as a theory for finding formulas for children’s stories. The material object used is the children’s story The Secret Seven Sapta Siaga. The techniques in data collection are literature study, reading, observation, and taking notes. The results of the study reveal that the children’s storybook The Secret Seven-Sapta Siaga by Enid Blyton is written with classic detective typology which in the story presents a hero with a final goal to be achieved. This detective children’s story has six main phases in the formulaic structure of the story namely, (1) the introduction of the detective. (2) crimes and leads. (3) inquiry. (4) Announcement of solutions. (5) explanation of solutions. And, (6)The end of the story. The form of the invention contained in the story pattern is the development of the detective genre in the form of a crime for attempted theft of goods.